Regionalism and regional security: paradoxes Asia-Pacific integration model (Journal of Philosophy Culture and Political Science, 2018)
In the article the problem of the relationship between the intensification of regional integration and the strengthening of on the example of the Asia-Pacific region is considered: the characteristics and specific features of the current model of the Asia-Pacific regionalism in terms of the need to establish more effective security tools and coherent sustainable development region are analyzed. Key words: regionalism, regional integration, regional security, Asia-Pacific region, model of integration.